Digital Financial Inclusion and Access to Financing for MSMEs: A Case Study of MSMEs in the Creative Sector in Lamongan - Lailiyah, Elliv Hidayatul; Zulyanti, Noer Rafikah; Fajri, Mega Barokatul; Syah, Imran; Abdullah, Addina Haque (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of digital financial inclusion in Indonesia has brought significant changes to the local economic system. The development of digital technology has fundamentally changed the way people access financial services. However, for MSMEs in the creative sector, access to formal financing remains a major challenge, particularly in Lamongan Regency, East Java. This study aims to understand in depth how digital financial inclusion practices affect MSMEs' access to financing in the creative sector, as well as the social, technological, and institutional factors that influence this process. This study used a qualitative approach with a case study design. Data were obtained through in depth interviews with 10 informants. Analysis was conducted using thematic analysis techniques to identify patterns of meaning and relationships between themes. The results show that digital financial inclusion expands access to financing through the convenience of fintech applications and mobile banking services, but its effectiveness is highly dependent on digital literacy, trust in digital systems, and local government support. Key inhibiting factors include limited internet access in rural areas, low understanding of digital risks, and minimal mentoring. This study emphasizes the importance of building an inclusive and adaptive digital financial ecosystem to the local context, through collaboration between businesses, the government, and digital financial institutions.